Effects of Amino Acid Substitutions at Position 115 on the Fidelity of Human Immunodeficiency Virus Type 1 Reverse Transcriptase - Boyer, Paul L. (American Society for Microbiology, 2000)
We compared the fidelity of wild-type human immunodeficiency virus type-1 (HIV-1) reverse transcriptase (RT) and two RT mutants, Y115F and Y115V. Although neither mutation had a large effect on the overall fidelity of the enzyme, both mutations altered the spectrum of mutations and the precise nature of the mutational hot spots. The effects of Y115V were greater than those of Y115F. When we compared the behavior of the wild-type enzyme with published data, we found that, in contrast to what has been published, misalignment/slippage could account for only a small fraction of the mutations we observed. We also found that a preponderance of the mutations (both transitions and transversions) resulted in the insertion of an A. Because we were measuring DNA-dependent DNA synthesis (plus-strand synthesis), this bias could contribute to the A-rich nature of the HIV-1 genome.